Hepcidin serum levels in HCV chronically mono-infected naïve patients, compared to healthy individuals - Leao, Ari Ben Hur Stefani; Ferronato, Maria da Graça; Kupski, Carlos; Schacher, Fernando Comunello; Machado, Denise Cantarelli; Álvares-da-Silva, Mario Reis (Clinical and Biomedical Research, 2018)
Introduction: Metabolism of iron is altered in patients infected with chronically Hepatitis C. The aim of this study is to compare compare the hepcidin levels in between individuais chronically infected with HCV and uninfected individuals. The aim of this study is to compare the hepcidin serum levels between individuals chronically infected with HCV and uninfected individuals. Methods: A cross-sectional study evaluating hepcidin serum levels of mono-infected HCV (n=29), naive, non-diabetic, non-cirrhotic and non-obese patients by means of ELISA, compared to uninfected patients (n=9) with the same characteristics. The degree of liver fibrosis, according to the METAVIR scale on liver biopsies, the lipid profile, the resistance insulin level, as calculated on HOMA-IR (homeostatic model assessment for insulin resistance), the interleukin-6 (IL-6) and the ferritin serum levels were also measured. Results: The levels of hepcidin were significantly lower in HCV patients compared to controls (8.4 pg/mL (±4.94) vs. 19.51 pg/mL (±5.51)) with p<0.001. The levels of ferritin and hepcidin did not show any relation. There was no difference between hepcidin levels in relation to viral genotype, viral load, IL-6 and degrees of fibrosis within HCV infected individuals. Conclusion: It is possible that hepatic iron overload in this population is explained by suppressed levels of hepcidin in patients with HCV. Keywords: Hepcidin; HCV; interleukin-6 (IL-6); mono-infected